Experimental study on thermoelectric generation Device based on accumulated temperature waste heat of coal gangue. (October 2022) - Peng, Hong; Li, Yang; Jia, XiangLong
Abstract: Coal gangue is industrial waste formed during coal production. Due to the accumulation of a large amount of heat inside, it is prone to spontaneous combustion. At present, the use of heat pipes to extract heat from coal gangue has become a relatively effective method, but the extracted heat has not been used rationally, causing damage to the natural environment. This paper proposes to use this part of thermal energy for thermoelectric conversion to realize thermoelectric generation, and on the basis of the experiment platform, and the factors that affect the maximum output power such as the arrangement mode, hierarchical structure and cold end heat dissipation mode of the thermoelectric module are studied. The paper also presents a thermoelectric conversion structure of "pipe in pipe", which reduces heat loss, increases the contact area between the heat pipe and the thermoelectric generation sheet, and improves the energy conversion efficiency and reduces energy waste, thus the output power of thermoelectric conversion increases. The use of thermoelectric conversion to convert waste heat energy into electrical energy is of great significance to the secondary use of energy.